MODEL PEMBELAJARAN SETS (SCIENCE, ENVIRONMENTAL, TECHNOLOGY, SOCIETY) BERBASIS BUDAYA LOKAL PADA PEMBELAJARAN IPA TERHADAP BERFIKIR KRITIS DAN PEDULI LINGKUNGAN - Erika Rosdiana; Edi Surya (Universitas Negeri Medan, 2022)
This study describes the contribution of SETS (Science, Environment, Technology, Society) model based on local culture on the improvement of creative thinking ability and environmental care of junior high school students in natural science instructional. The study was done by literature approaches by using relevant research results. By implementation of SETS model syntax with local culture enrichment, the research results showed there was the improvement of critical thinking of the junior high school student and also its environmental care in natural science learning process. Therefore, the natural science teachers were asked to implement the SETS model in natural science instruction in order to reach the learning of natural science objectives, especially in critical thinking and environmental care.